Aluminium 6061 is well known for its good tensile strength and high corrosion resistance due to the natural protective oxide layer formed on its surface. However, the phenomenon of corrosion can still occur, particularly in aggressive environments, leadin - Nur, Nur Asriyani (Journal of Energy, Material, and Instrumentation Technology, 2025)
Aluminium 6061 is well known for its good tensile strength and high corrosion resistance due to the natural protective oxide layer formed on its surface. However, the phenomenon of corrosion can still occur, particularly in aggressive environments, leading to material degradation. To further enhance corrosion resistance, a coating using the Plasma Electrolytic Oxidation (PEO) method with a concentrated solution of Na2SiO3, KOH, and EDTA was applied for 4 minutes. The addition of EDTA plays a crucial role not only in improving corrosion resistance but also in influencing the dielectric properties of the material, which subsequently affects the absorption of electromagnetic waves. Corrosion testing using the Tafel Polarization method revealed that the PEO coating with EDTA resulted in a more positive corrosion potential and a lower current density compared to untreated Aluminium 6061. Furthermore, EDTA enhances the porosity of the oxide layer, promoting the formation of micro-pores on the surface, which can trap corrosive agents and mitigate corrosion phenomena. Testing with a Vector Network Analyzer (VNA) at frequencies ranging from 8 GHz to 12 GHz demonstrated that the material exhibits an electromagnetic wave absorption of -1 dB. Overall, the application of PEO coating with EDTA significantly improves both corrosion resistance and electromagnetic wave absorption, making it suitable for various applications in the automotive, electronics, and energy industries